Optimasi Zeolit Alam Lampung (ZAL) Sebagai Penstabil Sediaan Antibakteri Esktrak Buah Mengkudu (Morinda citrifolia L.) - Laila Susanti; Lilik Koernia Wahidah; Pratika Viogenta (JFL : Jurnal Farmasi Lampung, 2018)
Noni fruit extract has been widely known as an antibacterial, but plant extracts are easily degraded by light, pH and temperature, thus reducing the antibacterial activity, zeolite is added to maintain the stability of the noni extract. This study uses an experimental method that is by comparing the inhibition zones that occur between noni fruit extract and noni + ZAL fruit extract and to test the stability of the preparation, the sample is heated at 40oC and then tested for antibacterial activity again. The statistical test results show the value of Asymp. Sig (0.003)